OSMANLI DÖNEMİ TÜRK MÜZİĞİNDE EKOL GELENEĞİ “HAMMÂMÎZÂDE İSMÂİL DEDE EFENDİ EKOLÜ” - Adar, Çağhan; Özkoç, Özkan (Fırat University, 2022)
Kökeni yüzlerce yıl öncesine dayanan Türk müziği, Orta Asya’dan başlayıp Anadolu’ya kadar gelen bir süreç geçirmiştir. Osmanlı ile birlikte Türk makam müziğinin tam anlamıyla yükselişe geçmeye başladığı dönem ise 18. yüzyıl olarak görülmektedir. Bu dönemden itibaren birçok bestekâr ve icracı yetişmeye başlamıştır. Özellikle Itri, Dilhayat Kalfa ve Ali Nutki Dede gibi bestekârlar ile yükselişe geçen bu müzik türü 19. yüzyılda zirveye ulaşmıştır. Bu dönemin en büyük bestekârlarından biride Hammami-zade İsmail Dede Efendi’dir. Hem kendi döneminde iz bırakan hem de sonraki dönemlerde yapmış olduğu bestelerle etkisini gösteren bir bestekârdır. Bu büyük besteciler tarafından verilen müzik eğitimi Osmanlı döneminde Türk makam müziğinin aktarılmasında en önemli vasıta olan meşk sistemi ile yapılıyordu. Sonrasında bu tavrı alan öğrenci kendi öğrencilerine bunu aktarır ve süreç devam ederdi. Bu sisteme de Türk makam müziğinde ekol sistemi denilmekteydi. Bu çalışmada Türk müziği ekol geleneği incelenmiş, Hammami-zade İsmail Dede Efendi’den Lemi Atlı’ya kadar olan ekolün besteleme teknikleri, varsa değişimleri ve benzerlikleri ortaya çıkarılmıştır. Çalışmada, bu ekolün ortak olarak bestelemiş olduğu karcığar makamından seçilen eserler incelenmiş ve bulgulara ulaşılmıştır. Çalışmanın, alanında özgün olduğu ve bu alanda çalışma yapacaklara kaynak teşkil edeceği düşünülmektedir.

Turkish music, whose origins date back hundreds of years, has gone through a process starting from Central Asia to Anatolia. Turkish music, which is a definition in itself, began to be divided into two groups with the Ottoman Empire, the music made by the people was called folk music and the music performed in the palace had been said Turkish classical music or classical Turkish music. The period when Turkish art music started to rise fully with the Ottoman Empire is seen as the 18th century. Since this period, many composers and performers have been trained. This type of music, which rose especially with composers such as Itri, Dilhayat Kalfa and Ali Nutki Dede, reached its peak in the 19th century. One of the greatest composers of this period was Hammami-zade İsmail Dede Efendi. He is a composer who left a mark in his own period and showed his influence with the compositions he made in the following periods. The musical education given by these great composers was being done out with the mesk system, which was the most important means of transferring Turkish art music in the Ottoman period. With the work done with the mesk system, the teacher would explain to his students how to perform the work by exemplifying. Later, the student who took this attitude would convey it to his own students and the process would continue. This system was called the school system in Turkish classical music. In this study, the tradition of the Turkish music school was examined, and the composition techniques of the school from Hammami-zade İsmail Dede Efendi to Lemi Atlı, if any, and its similarities were tried to be revealed. In the study, the works selected from Karcığar makam, which was composed jointly by this school, were examined and findings were reached. It is thought that the study is original in its field and will be a resource for those who will work in this field.
School Tradition In Turkish Music In The Ottoman Period “Hammâmîzâde İsmâil Dede Efendi School”